1995
DOI: 10.1083/jcb.128.1.171
|View full text |Cite
|
Sign up to set email alerts
|

Roles of hepatocyte growth factor/scatter factor and the met receptor in the early development of the metanephros.

Abstract: Abstract. Several lines of evidence suggest that hepatocyte growth factor/scatter factor (HGF/SF), a soluble protein secreted by embryo fibroblasts and several fibroblast lines, may elicit morphogenesis in adjacent epithelial cells. We investigated the role of HGF/SF and its membrane receptor, the product of the c-met protooncogene, in the early development of the metanephric kidney. At the inception of the mouse metanephros at embryonic day 11, HGF/SF was expressed in the mesenchyme, while met was expressed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
160
0

Year Published

1996
1996
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 300 publications
(163 citation statements)
references
References 52 publications
3
160
0
Order By: Relevance
“…Two of these lines also showed an increased mitogenic response to exogenous HGF/SF Furthermore, transfection of human Met and HGF/SF genes into 3T3 cells results in cell lines highly tumorigenic in nude mice, as a result of autocrine stimulatory mechanisms (Rong et al, 1992). Mesangial fibroblasts also both secrete HGF/SF and synthesize Met (Kolatsi-Joannou et al, 1995). The addition of HGF/SF causes an increase in the bipolar morphology of mesangial cells, suggesting an autocrine role of HGF/SF in maintaining fibroblast morphology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two of these lines also showed an increased mitogenic response to exogenous HGF/SF Furthermore, transfection of human Met and HGF/SF genes into 3T3 cells results in cell lines highly tumorigenic in nude mice, as a result of autocrine stimulatory mechanisms (Rong et al, 1992). Mesangial fibroblasts also both secrete HGF/SF and synthesize Met (Kolatsi-Joannou et al, 1995). The addition of HGF/SF causes an increase in the bipolar morphology of mesangial cells, suggesting an autocrine role of HGF/SF in maintaining fibroblast morphology.…”
Section: Discussionmentioning
confidence: 99%
“…HGF/SF acts via a paracrine mechanism of action. More generally, in early development, coexpression of the HGF/SF and c-Met genes precedes separate expression in adjacent tissues, which occurs as organogenesis proceeds (Sonnenberg et al, 1993;Woolf et al, 1995;Andermacher et al, 1996). Therefore the sarcomatoid mesothelioma cell lines may reflect a more primitive mesenchymal developmental state.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of increase observed in both cell growth (155% increase compared with untreated controls) and candidate gene mRNA levels after HGF/SF exposure are entirely consistent with the highly differentiated, untransformed nature of the PTECs used which, unlike many tumour cell lines, do not display large changes in their growth rate after growth factor exposure. Furthermore, in view of the powerful mitogenic and morphogenic effects of HGF/SF on PTECs (Cantly et al, 1994;Woolf et al, 1995), studies in which the observed changes in gene expression are related to cell cycle, proliferative and morphogenic parameters would be of further interest.…”
Section: Discussionmentioning
confidence: 99%
“…Serum levels of HGF/SF are rapidly induced after renal injury or failure (Chang et al, 1996). HGF/SF is also believed to have a role in normal renal development and is the most potent renal tubular cell mitogen identified so far (Harris et al, 1993;Cantley et al, 1994;Woolf et al, 1995). Precise details of how HGF/SF promotes renal tubular cell mitogenesis are not known, although HGF/SF stimulation has been reported to increase in vivo expression of the VEGF gene in non-renal systems (Silvagno et al, 1995).…”
mentioning
confidence: 99%
“…Signaling via this receptorligand pair has been shown to affect a wide range of biological activities, including cell scattering and growth, morphogenic differentiation, angiogenesis, and mesenchymal to epithelial conversion (3,5,16,18,19,25,29,44,56,57). HGF/SF-Met signaling in vivo has been shown to be essential for normal embryological development (1,48,58) and is believed to play a role in tissue regeneration and wound healing, as well as in the development of the nervous system, kidney, muscle, mammary gland, and liver (1,25,26,35,47,48,50,54,63,65). While HGF/SF-Met signaling clearly mediates a variety of normal cellular processes, this receptor-ligand pair has also been implicated in the generation and spread of tumors (22).…”
mentioning
confidence: 99%